2012
DOI: 10.5923/j.ajee.20120206.02
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Screening of Dye Degrading Micro-organisms from the Effluents of Dye and Textile Industries at Surat

Abstract: Text ile dyes have been used since the Bronze Age. They also constitute a prototype 21 st -century speciality chemicals market. Effluent and soil samp les were collected fro m textile industry at Surat. The pH, temperature, BOD, COD, Nitrate and Nitrite values were co mpared with the values given by the Bureau of Indian Standards. The culture med iu m was designed and standardized in the laboratory for the isolation and degradation of the dyes. Pure cultures were screened on the basis of colony morphology. Thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 43 publications
0
4
0
1
Order By: Relevance
“…The metabolic activity of any microorganisms affecting the decolorization efficiency can be improved by optimizing the environmental parameters such as pH, temperature, and inoculum size (Varala, Dharanija, Satyavathi, Rao, & Parthasarathy, 2016). For the optimization of decolorizing parameters, a three-factor design with three independent variables was applied using BBD matrix of RSM to exclude the limitation of one-factor-at-a-time (OFAT) method (Tang, Xiao, Xu, & Zhang, 2013;Thakur, Khan, & Doshi, 2012). To the best of our knowledge, no optimization studies have been reported with the RSM involving the BBD matrix aimed at the decolorization of Indanthrene Blue RS dye with the isolated Bacillus sp.…”
Section: Introductionmentioning
confidence: 99%
“…The metabolic activity of any microorganisms affecting the decolorization efficiency can be improved by optimizing the environmental parameters such as pH, temperature, and inoculum size (Varala, Dharanija, Satyavathi, Rao, & Parthasarathy, 2016). For the optimization of decolorizing parameters, a three-factor design with three independent variables was applied using BBD matrix of RSM to exclude the limitation of one-factor-at-a-time (OFAT) method (Tang, Xiao, Xu, & Zhang, 2013;Thakur, Khan, & Doshi, 2012). To the best of our knowledge, no optimization studies have been reported with the RSM involving the BBD matrix aimed at the decolorization of Indanthrene Blue RS dye with the isolated Bacillus sp.…”
Section: Introductionmentioning
confidence: 99%
“…They have less operational cost, are eco-friendly, and under optimal operating conditions produce less sludge compared to other methodologies [18,19] . This biodegradation process has turned out to be a promising method as it completely decolorizes the dye and transforms them into a non-toxic chemical form [20,21] . Under optimized, aerobic or anaerobic conditions using microorganisms, a significantly high percentage of decolorization and degradation of dyes can be achieved [22,23,24] .…”
Section: Introductionmentioning
confidence: 99%
“…[6,7,10]. Такі дослідження можуть бути важливими не лише при ви-вченні нових та малодосліджених мікроорганізмів, а також бути необхідними для періодичної перевірки культур на чистоту у процесі виготовлення нафто-окиснювального біопрепарату для біоремедіації довкілля [12].…”
unclassified